Speciation and isotopic analysis of zinc in size-fractionated aerosol samples related to its source and chemical processes. (1st February 2023) - Natori, Sachika; Fujiwara, Masatomo; Kurisu, Minako; Tanimizu, Masaharu; Iizuka, Tsuyoshi; Takahashi, Yoshio
Abstract: Zinc (Zn) in aerosols plays important roles for biological activity and attracts public attention from the perspective of environmental measures. Because of its high volatility and water solubility, Zn is readily released into the atmosphere by human activities and supplied to natural water. To explore the origin and formation process of Zn in atmospheric aerosols, it is important to investigate isotopic (= δ 66 Zn) and speciation information of Zn in size-fractioned aerosols. We measured light δ 66 Zn (e.g., δ 66 ZnIRMM = −1.32‰ as the lowest value; IRMM-3702 is used for the normalization in this study) mainly for the particles ranging from 0.65 to 4.7 μm for the samples collected at Tsukuba, Chiba, and a motorway tunnel (Yasumiyama Tunnel in Hiroshima) in particular for the samples collected in 2002, but δ 66 ZnIRMM in the particle sizes increased above −0.8‰ for the samples collected in 2011 and 2016. Zn species in aerosols were estimated based on X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopy, suggesting that (i) Zn oxalate and sulfate and (ii) Zn oxide, sulfide, and carbonate are main Zn species in fine and coarse particles, respectively. In particular, Zn chloride was found mainly in the middle particle size range (2.1–4.7 μm), which corresponds to the range with light δ 66 Zn, suggesting that the light δ 66 Zn was caused by emission of Zn chloride during artificial combustion processes in accordance with other studies. The origins of Zn in aerosols are assumed to have three endmembers; (A) tire and brake wears and road dust, (B) industrial emissions, and (C) vehicular exhaust. Their formation mechanisms are related to vaporization and mixing processes based on the results of combined analysis of atmospheric concentration, speciation, and isotopic composition of Zn with different particle sizes. These trends could be successfully interpreted by species-specific δ 66 Zn values: component (A) consisting mainly of Zn oxide and sulfide with relatively heavier δ 66 Zn, component (B) Zn chloride and sulfate secondarily formed in the droplet mode having lightest δ 66 Zn among all the species, and (C) Zn oxalate with δ 66 Zn closer to 0‰ due to its emission by the complete combustion in vehicle engines. Species-specific Zn isotope data obtained by the simultaneous application of speciation and isotopic analyses of Zn in size-fractionated aerosols complementary provide novel information on the initial generation and secondary processes for the formation of Zn species in the aerosols. Highlights: Zn in aerosols in the range of 0.65–4.7 μm collected at Tsukuba, Japan in 2002 had remarkably light δ 66 Zn. Simultaneous application of speciation and isotopic analyses of Zn in size-fractionated aerosols can be a powerful tool to estimate the origin and formation processes of Zn in aerosols. Species-specific δ 66 Zn can be explained by (A) Zn oxide and sulfide in tire and brake wears and road dust, (B) Zn chloride and sulfate related to industrial emissions, and (C) Zn oxalate from vehicular exhaust.